Recurrent rhabdomyolysis caused by palmitoyltransferase II (CPT-2) deficiency but complete normal acylcarnitine profile: A patient presentation and review of the literature - Chih-Hsuan Lu; Chia-Feng Yang; Yun-Ru Chen; Yann-Jang Chen; Yung-Hsiu Lu; Dau-Ming Niu (Molecular Genetics and Metabolism Reports)
Recurrent rhabdomyolysis, marked by skeletal muscle breakdown, can stem from various causes, including genetic disorders. We detail a patient of a 22-year-old male with carnitine palmitoyltransferase II (CPT-2) deficiency manifesting recurrent rhabdomyolysis despite normal acylcarnitine profiles. Whole-genome sequencing identified two CPT2 gene variants: c.338C > T and c.482G > A, confirming the diagnosis. We conducted a case report and a comprehensive literature review encompassing 262 articles related to CPT-2 deficiency available on PubMed. The review detailed 245 cases across various forms, including lethal neonatal, severe infantile hepatocardiomuscular, and myopathic forms. The study highlighted the variability and complexity of CPT-2 deficiency phenotypes, emphasizing correlations between variants and phenotypes as well as gender distribution. Although the CPT-2 deficiency genotype does not entirely predict phenotype severity, it remains informative for most patients, assisting in assessing the severity linked to each genetic variant. The results of our study offer crucial insights into evaluating the severity associated with individual genetic variants. Notably, our patient displayed normal acylcarnitine profiles between illness episodes, indicating possible profile abnormalities only during active disease states.We propose the collection of additional blood samples for acylcarnitine analysis during episodes of rhabdomyolysis without delay in all patients presenting with rhabdomyolysis of unknown cause as a crucial diagnostic strategy. This approach may unveil unexpected underlying diseases, enabling early and accurate diagnoses.